1993
DOI: 10.1128/iai.61.4.1547-1552.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a salivary agglutinin-binding domain within cell surface adhesin P1 of Streptococcus mutans

Abstract: DNA encoding the alanine-rich region (A-region) of the cell surface adhesin, P1, from Streptococcus mutans was subcloned and expressed as a fusion protein with the maltose-binding protein (MBP) of Escherichia coli. The A-region fusion protein was shown to competitively inhibit both adherence of S. mutans to salivary agglutinin-coated hydroxyapatite and fluid-phase agglutinin-mediated aggregation of this organism. MBP alone or an MBP-paramyosin fusion protein was not inhibitory. Proteolytic cleavage of the fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 32 publications
6
76
0
1
Order By: Relevance
“…Most species of oral streptococci express on their cell surface a high-molecular-mass polypeptide of the I/II family, which is a multifunctional adhesin with multiple ligand binding sites. This protein binds chiefly to salivary constituents such as salivary glycoproteins (Crowley et al, 1993) either in the fluid phase or adsorbed to hydroxyapatite, to human epithelial, endothelial and monocytic cells, and binding to cells occurs via lectin interactions specific for N-acetyl neuraminic acid and fucose (Soell et al, 1994;Vernier et al, 1996). Moreover, we and others (Love et al, 1997;Sciotti et al, 1997) have demonstrated the capacity of protein I/II to bind to extracellular and matrix proteins such as collagen I, laminin and fibronectin, which suggests the propensity of the bacteria or bacterial components to disseminate and persist in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Most species of oral streptococci express on their cell surface a high-molecular-mass polypeptide of the I/II family, which is a multifunctional adhesin with multiple ligand binding sites. This protein binds chiefly to salivary constituents such as salivary glycoproteins (Crowley et al, 1993) either in the fluid phase or adsorbed to hydroxyapatite, to human epithelial, endothelial and monocytic cells, and binding to cells occurs via lectin interactions specific for N-acetyl neuraminic acid and fucose (Soell et al, 1994;Vernier et al, 1996). Moreover, we and others (Love et al, 1997;Sciotti et al, 1997) have demonstrated the capacity of protein I/II to bind to extracellular and matrix proteins such as collagen I, laminin and fibronectin, which suggests the propensity of the bacteria or bacterial components to disseminate and persist in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure among the PAc family is well conserved and consists of a leader sequence, two repeat regions (A re-gion; alanine-rich region, P region; proline-rich region), a variable region (V region) and a cell anchor region. The large regions containing each A and P region in PAc have been suggested to play key roles in interaction with salivary components [12] and in adherence of S. mutans to saliva-coated hydroxyapatite [13], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…P1 also interacts with soluble fluid-phase components promoting aggregation and, presumably, elimination of S. mutans cells from the oral cavity (Ericson & Rundegren, 1983;Demuth et al, 1988;Koga et al, 1990). These dual roles of S. mutans P1 are contributed to by amino acid residues within P1 39-512 (Crowley et al, 1993;Nakai et al, 1993;Hajishengallis et al, 1998;Matsumoto-Nakano et al, 2008). Aggregation and adherence of S. mutans are inhibited by different anti-P1 monoclonal antibodies (Brady et al, 1992), indicating that the composite specificity of the host immune response would represent a key feature in determining the neutralization activity of elicited antibodies to a specific vaccine immunogen.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion of S. mutans to immobilized saliva, and adherence inhibition mediated by different serum samples, were based on a method described previously (Jakubovics et al, 2005). As a positive control reaction for inhibition of P1-mediated bacterial adhesion, we used 3 mM EDTA added to the bacterial cell suspension to interrupt the calcium-dependent interaction between P1 and gp340, as described previously (Crowley et al, 1993). Nonimmune serum was used as a negative control and the S. mutans strain PC3370 devoid of P1 was also used as a negative control.…”
Section: Inhibition Of Smutans Adhesion To Immobilized Salivamentioning
confidence: 99%